Building a Cadastral Map of Europe through the INSPIRE and Other Related Initiatives - Vlado Cetl; Sanja Šamanović; Olga Bjelotomić Oršulić; Anka Lisec (Land, 2023)
Digital cadastral maps with accompanying land-related attributes have become a fundamental dataset for many application fields, e.g., spatial planning and development, protecting state lands, securing of land tenure, facilitating land reforms, agriculture, forestry, land management, taxation, etc. In order to fulfil its main objectives, cadastral data needs to be available and accessible, which is, among the others, emphasized also within the United Nations Framework for Effective Land Administration (FELA). This is not only important on the national level but also beyond, including at the European level where use cases and consequently demand for pan-European data sets have evolved in recent years. In order to satisfy these needs, several initiatives regarding cadastral and other geospatial data have been launched in the last 20 years. It started with the Permanent Committee on Cadastre in the European Union, the European Land Information Service, INSPIRE, UN-GGIM Europe and recent European policies on open data and high-value datasets. Our main question is, did those initiatives result in the possibility of building a cadastral map of Europe or not? Is it possible to create a cadastral map of Europe on the desktop or an open online GIS application? Within the paper, we take the opportunity to reflect on the development and implementation of European spatial data infrastructure (INSPIRE) with the main focus on the availability and accessibility of cadastral data. We also take into consideration other European initiatives related to cadastral data. The overall findings show that there is still work to be carried out. Technological developments and recent policy initiatives will certainly be drivers for future improvement.